Health and wellness in 19th-century America - Waller, John 1972- (Health and wellness in daily life, 2014)
"This book provides a comprehensive description of what being sick and receiving "medical care" was like in 19th-century America, allowing modern readers to truly appreciate the scale of the improvements in healthcare theory and practice"--